Determinants of expected stock returns: Large sample evidence from the German market - Sabine Artmann; Philipp Finter; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2011)
This paper conducts a comprehensive asset pricing study based on a unique dataset for the German stock market. For the period 1963 to 2006 we show that value characteristics and momentum explain the cross-section of stock returns. Corresponding factor portfolios have significant premiums across various double-sorted characteristic-based test assets. In a horse race of competing asset pricing models the Fama-French 3-factor model does a poor job in explaining average stock returns. The Carhart 4-factor model performs much better, but a 4-factor model containing an earnings-to-price factor instead of a size factor does even slightly better.
Keywords: G12; 330; asset pricing; characteristics; risk factors; multifactor models; Germany